The memory of an outrageous public health scandal - Rolim, Sally de França Lacerda; Silva, Claudio Gleidiston Lima da; Ramirez, Fabian Danilo Unigarro; Pinheiro, Raul Cesar Fortaleza; Paula, Juliane dos Anjos de; Lima, Nádia Nara Rolim; Rolim Neto, Modesto Leite (Avanços em Medicina, 2025)
Introduction: Manaus is an isolated city, localized in the hearth of the Amazonas rainforest, with two million inhabitants, a big territorial extension, distant from neighbor cities and next to the shores of Negro and Solimões rivers. The access overland is difficult, which obligates the oxygen tanks be transported by river or air. This created and enormous logistical problem, added to the neglect of the Federal Government with the northern region of the country. Objective: Analyze what are the psychiatric repercussions on the explosion of in the lack of oxygen in Manaus, capital of the Amazonas, Brazil. Methods: Studies were identified using large-circulation international journals. Results: A scandal is happening. This situation is creating a grief community – particular grief became a common and public one – to the memory of an outrageous public health scandal. Therefore, dramatic stories of families of patients and the overwhelmed healthcare professionals shared on the social media and local press brings glimpses of the angst of this chaos. An entire wing of patients died caused by the oxygen depletion. Conclusion: This situation is causing a collective hysteria, taking healthcare workers and families of patients to desperation. Fear appears to be a consequence of the feeling of powerlessness. Anxiety levels are really elevated causing direct side effects to another mental health measures.